2013
DOI: 10.2174/157339913805076472
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Exenatide as a Diabetes Therapeutic

Abstract: Type 2 diabetes (T2DM) is a disease of epidemic proportion associated with significant morbidity and excess mortality. Optimal glucose control reduces the risk of microvascular and possibly macrovascular complications due to diabetes. However, glycemic control is rarely optimal and several therapeutic interventions for the treatment of diabetes cause hypoglycemia and weight gain; some may exacerbate cardiovascular risk. Exenatide (synthetic exendin-4) is a glucagon-like peptide-1 receptor (GLP-1R) agonist deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 124 publications
(245 reference statements)
2
31
0
Order By: Relevance
“…Synthetic analogs of exendin-4 have been approved for diabetes therapy, and their efficacy is mostly linked to their resistance to degradation by DPP-4, the enzyme that quickly degrades endogenous GLP-1. 114 Later studies suggested that epigenetic effects, such as DNA methylation and/or histone modifications, could mediate the effects of exendin-4 and its synthetic analogs. 115 However, it is not known whether these peptides exert the anti-diabetic effect by inducing epigenetic changes, and their classification as epidrug remains hypothetical.…”
Section: Other Potential Epidrugsmentioning
confidence: 99%
“…Synthetic analogs of exendin-4 have been approved for diabetes therapy, and their efficacy is mostly linked to their resistance to degradation by DPP-4, the enzyme that quickly degrades endogenous GLP-1. 114 Later studies suggested that epigenetic effects, such as DNA methylation and/or histone modifications, could mediate the effects of exendin-4 and its synthetic analogs. 115 However, it is not known whether these peptides exert the anti-diabetic effect by inducing epigenetic changes, and their classification as epidrug remains hypothetical.…”
Section: Other Potential Epidrugsmentioning
confidence: 99%
“…In contrast, rosiglitazone was associated with a two-fold increase in insulin sensitivity, while exenatide twice daily had no significant insulin-sensitizing effect. β-cell function was further evaluated using the disposition index, which is calculated from hyperglycemic and glucagon secretion [14], which in turn reduces hepatic glucose production [15]. Furthermore, GLP-1RAs slow gastric emptying, decrease food intake, and promote satiety [14].…”
Section: Functional Studiesmentioning
confidence: 99%
“…β-cell function was further evaluated using the disposition index, which is calculated from hyperglycemic and glucagon secretion [14], which in turn reduces hepatic glucose production [15]. Furthermore, GLP-1RAs slow gastric emptying, decrease food intake, and promote satiety [14]. Because native GLP-1 and GLP-1RAs were shown to reduce apoptosis and/or increase cellular proliferation and β-cell mass in rodent models of diabetes and insulin resistance [16,17], it was hypothesized that GLP-1RAs may modify β-cell function in patients with T2D.…”
Section: Functional Studiesmentioning
confidence: 99%
“…[1][2][3] In 2012, the US FDA approved a long-acting formulation of exenatide for once-weekly administration that can be administered regardless of meal times; 4 European Medicines Agency approval occurred in 2011. The long-acting, sustained release of exenatide is achieved by dispersion of the parent exenatide molecule in poly-(D,L-lactide-co-glycolide) polymer microspheres approximately 0.06 mm in diameter.…”
mentioning
confidence: 99%
“…After injection of microspheres into the subcutaneous space, gradual biodegradation of the polymer matrix into CO 2 and H 2 O releases exenatide continuously over an extended duration. With regular once-weekly dosing, mean exenatide levels exceed the minimal effective concentration (50 pg/mL) in 2 weeks and achieve steady state in 6-7 weeks, resulting in consistent concentrations of exenatide.…”
mentioning
confidence: 99%